Toward real-time margin assessment in breast-conserving surgery with hyperspectral imaging - Lynn-Jade S. Jong; Dinusha Veluponnar; Freija Geldof; Joyce Sanders; Marcos Da Silva Guimaraes; Marie-Jeanne T. F. D. Vrancken Peeters; Frederieke van Duijnhoven; Henricus J. C. M. Sterenborg; Behdad Dashtbozorg; Theo J. M. Ruers (Scientific Reports)
Abstract Margin assessment in breast-conserving surgery (BSC) remains a critical challenge, with 20-25% of cases resulting in inadequate tumor resection, increasing the risk of local recurrence and the need for additional treatment. In this study, we evaluate the diagnostic performance of hyperspectral imaging (HSI) as a non-invasive technique for assessing resection margins in ex vivo lumpectomy specimens. A dataset of over 200 lumpectomy specimens was collected using two hyperspectral cameras, and a classification algorithm was developed to distinguish between healthy and tumor tissue within margins of 0 and 2 mm. The proposed approach achieved its highest diagnostic performance at a 0 mm margin, with a sensitivity of 92%, specificity of 78%, accuracy of 83%, Matthews correlation coefficient of 68%, and an area under the curve of 89%. The entire resection surface could be imaged and evaluated within 10 minutes, providing a rapid and non-invasive alternative to conventional margin assessment techniques. These findings represent a significant advancement toward real-time intraoperative margin assessment, highlighting the potential of HSI to enhance surgical precision and reduce re-excision rates in BCS.